Application of Location-Based Service (LBS) in The Information System for Determining The Location of Craft Shops in The City of Tasikmalaya Based on Android - Cahyadi, Cepi; Jaelani, Rusani (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2024)
Information is data that is necessary and essential in the era of technological development. One of the information needs is to find the location of craft shops in Tasikmalaya City, especially for foreigners who need information to buy craft products who do not know the location. Currently, information is only created manually through official documents in the form of paper posted on walls or in public places where people gather. Based on the description of the problems obtained, it is necessary to improve services in the information sector, designing a manual craft shop location search information system which will be developed into a technology-based digital information system using the Android Studio application and MySQL database. With the Location Service (LBS) and Global Positioning System (GPS) methods, with this system, users will be given location information and routes to their destination points easily to craft shop locations in Tasikmalaya City. All of these systems provide convenience in conveying information on searching for the location of craft shops in the city of Tasikmalaya.